2017
DOI: 10.1042/cs20170047
|View full text |Cite
|
Sign up to set email alerts
|

Human DPSCs fabricate vascularized woven bone tissue: a new tool in bone tissue engineering

Abstract: Human dental pulp stem cells (hDPSCs) are mesenchymal stem cells that have been successfully used in human bone tissue engineering. To establish whether these cells can lead to a bone tissue ready to be grafted, we checked DPSCs for their osteogenic and angiogenic differentiation capabilities with the specific aim of obtaining a new tool for bone transplantation. Therefore, hDPSCs were specifically selected from the stromal–vascular dental pulp fraction, using appropriate markers, and cultured. Growth curves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 32 publications
4
80
0
1
Order By: Relevance
“…In recent years, tissue engineering has been widely focused and considered an important approach to restore damaged tissues and organs . The emergence of tissue engineering technology enables the successful isolation of dental pulp stem cells (DPSCs) and the use of DPSCs for repair of bone tissues or dentin‐pulp tissue and even for the construction of natural teeth . DPSCs are tissue‐specific stem cells with a high proliferation rate, self‐renewal capability and high accessibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, tissue engineering has been widely focused and considered an important approach to restore damaged tissues and organs . The emergence of tissue engineering technology enables the successful isolation of dental pulp stem cells (DPSCs) and the use of DPSCs for repair of bone tissues or dentin‐pulp tissue and even for the construction of natural teeth . DPSCs are tissue‐specific stem cells with a high proliferation rate, self‐renewal capability and high accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The emergence of tissue engineering technology enables the successful isolation of dental pulp stem cells (DPSCs) and the use of DPSCs for repair of bone tissues or dentin-pulp tissue and even for the construction of natural teeth. [5][6][7][8] DPSCs are tissuespecific stem cells with a high proliferation rate, self-renewal capability and high accessibility. Studies have demonstrated that DPSCs can differentiate to multiple cell lineages, including osteoblast, 9 chondrocytes, 10 odontoblasts 11,12 and neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the easily accessible source of dental tissues, dental-derived stem cells are considered suitable candidates for tissue engineering applications [1, 2]. Dental pulp stem cells (DPSCs), isolated from human dental pulp tissue, possess multilineage differentiation potential, including osteogenic, dentinogenic, adipogenic, chondrogenic, myogenic, and neurogenic differentiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) can isolated various sources including bone marrow, trabecular and cortical bone, adipose tissue, skeletal muscle, peripheral blood, umbilical cord blood, and dental pulp and differentiate into multi-lineage according to sources such as osteoblast, chondrocytes, adipocytes, cardiomyocytes, tenocytes, muscle cells, fibroblast, and neuron [1][2][3][4][5]. Over the past decades, there has been tremendous focus on attempts to repair cardiac tissue with stem cell transplantation, and MSCs have been widely studied in both animal models and clinical trials [6,7].…”
Section: Introductionmentioning
confidence: 99%